Priority of Agricultural Sub-Sector Development Increasing Economic Growth in Sidenreng Rappang Regency - Rahmani; Tri Rezki Aulia; Nurhikma Tasri; Sri Wardhany Ali (IECON: International Economics and Business Conference, 2023)
The agricultural sector is a very strategic factor, which is the basis of the people's economy, especially in rural areas, dominates the lives of the majority of the population, absorbs more than half of the total workforce and even becomes a safety valve during the Indonesian crisis. The agricultural sector has an important role in the Indonesian economy. This can be measured from the share of the agricultural sector in the formation of gross domestic product (GDP), providing employment, a source of income for the majority of Indonesian people and poverty alleviation. Development theory states that the agricultural sector is the engine of growth both in terms of supplying raw materials, food ingredients, as well as purchasing power for products produced by other sectors. From the results of the research that has been done, it is known that the priority scale in the development of the Agriculture, Forestry and Fishery sectors in Sidenreng Rappang Regency is more intensely increased by utilizing or utilizing various existing resources, and having an orientation that is comprehensive, complete, but still adhering to the principle priority, because the Agriculture sector in Sidenreng Rappang Regency has fluctuated from 2015 to 2020. It is known that from 2015 to 2018 it has increased from year to year, but in 2019 to 2020 it has decreased and in 2021 to 2022 has increased, the decline in contribution to the agricultural sector from 2018 to 2019 was due to a pandemic or disease transmission which limited community activities.